Consequences of Mixotrophy on Cell Energetic Metabolism in Microchloropsis gaditana Revealed by Genetic Engineering and Metabolic Approaches - Bo, Davide Dal; Magneschi, Leonardo; Bedhomme, Mariette; Billey, Elodie; Deragon, Etienne; Storti, Mattia; Menneteau, Mathilde; Richard, Christelle; Rak, Camille; Lapeyre, Morgane; Lembrouk, Mehdi; Conte, Melissa; et al. (Frontiers in Plant Science, 2021)
Algae belonging to the Microchloropsis genus are promising organisms for biotech purposes, being able to accumulate large amounts of lipid reserves. These organisms adapt to different trophic conditions, thriving in strict photoautotrophic conditions, as well as in the concomitant presence of light plus reduced external carbon as energy sources (mixotrophy). In this work, we investigated the mixotrophic responses of Microchloropsis gaditana (formerly Nannochloropsis gaditana). Using the Biolog growth test, in which cells are loaded into multiwell plates coated with different organic compounds, we could not find suitable substrate for Microchloropsis mixotrophy. By contrast, addition of the Lysogeny Broth (LB) to the inorganic growth medium increased growth, enhancing respiratory activity at the expenses of photosynthetic performances. To further dissect the role of respiration in Microchloropsis mixotrophy, we focused on the mitochondrial Alternative Oxidase (AOX), a protein involved in energy management in other algae prospering in mixotrophy. Knocking-out the AOX1 gene by TALE-N led to the loss of capacity to implement growth upon addition of LB supporting the hypothesis that the effect of this medium was related to a provision of reduced carbon. We conclude that mixotrophic growth in Microchloropsis is dominated by respiratory rather than by photosynthetic energetic metabolism, and discuss possible reasons for this behaviour in relationship with fatty acid breakdown via β-oxidation in this oleaginous alga.